Genome-Wide Meta-Analyses of Plasma Renin Activity and Concentration Reveal Association With the Kininogen 1 and Prekallikrein Genes. (February 2015) - Lieb, Wolfgang; Chen, Ming-Huei; Teumer, Alexander; de Boer, Rudolf A.; Lin, Honghuang; Fox, Ervin R.; Musani, Solomon K.; Wilson, James G.; Wang, Thomas J.; Völzke, Henry; Petersen, Ann-Kristin; Meisinger, Christine; et al.
Abstract : Background—: The renin–angiotensin–aldosterone system (RAAS) is critical for regulation of blood pressure and fluid balance and influences cardiovascular remodeling. Dysregulation of the RAAS contributes to cardiovascular and renal morbidity. The genetic architecture of circulating RAAS components is incompletely understood. Methods and Results—: We meta-analyzed genome-wide association data for plasma renin activity (n=5275), plasma renin concentrations (n=8014), and circulating aldosterone (n=13289) from ⩽4 population-based cohorts of European and European-American ancestry, and assessed replication of the top results in an independent sample (n=6487). Single-nucleotide polymorphisms (SNPs) in 2 independent loci displayed associations with plasma renin activity at genome-wide significance ( P <5×10 −8 ). A third locus was close to this threshold (rs4253311 in kallikrein B [KLKB1], P =5.5×10 −8 ). Two of these loci replicated in an independent sample for both plasma renin and aldosterone concentrations (SNP rs5030062 in kininogen 1 [KNG1]: P =0.001 for plasma renin, P =0.024 for plasma aldosterone concentration; and rs4253311 with P <0.001 for both plasma renin and aldosterone concentration). SNPs in the NEBL gene reached genome-wide significance for plasma renin concentration in the discovery sample (top SNP rs3915911; P =8.81×10 −9 ), but did not replicate ( P =0.81). No locus reached genome-wide significance for aldosterone. SNPs rs5030062 and rs4253311 were not related to blood pressure or renal traits; in a companion study, variants in the kallikrein B locus were associated with B-type natriuretic peptide concentrations in blacks. Conclusions—: We identified 2 genetic loci ( kininogen 1 and kallikrein B ) influencing key components of the RAAS, consistent with the close interrelation between the kallikrein–kinin system and the RAAS. Abstract : Supplemental Digital Content is available in the text.